Women's overload during the pandemic: Unpaid care work, financial well-being, and stress - Bulog, Ivana; Pepur, Sandra; Smiljanić, Ana Rimac (Management : Journal of Contemporary Management Issues, 2022)
This study examines the relationship between unpaid care work, financial well-being, and stress levels among women during the COVID-19 pandemic. The pandemic caused downturns in the economies of countries worldwide and led to uncertainties and changes that created conditions for increased stress levels and consequently impaired well-being. In addition to social distancing and lockdown measures to cope with the virus, working from home, home schooling, caring for sick and older family members, and financial problems have added burdens and have proven to be additional personal and family stressors. The findings are based on an online survey conducted among women during the second lockdown in Croatia. Additional unpaid care work and lower financial well-being affect the increased stress felt by women during the pandemic. This is especially pronounced among women who are more involved in paid work. During the pandemic, additional unpaid care work, increased involvement in paid work, and jeopardized financial well-being were stressors for women. Our results indicate the importance of women s free time for their own and their families 'well-being.
Keywords: 2000 à aujourd'hui; 2020-2029; anxiété; care; conciliation famille-travail; covid-19; croatie; discipline; europe; famille; pandémie; projet charge mentale; périodes historiques; régions géographiques; santé; sciences de la gestion; thématiques; travail; travail gratuit; économie